Automatic Detection of Alzheimer’s Disease from Magnetic Resonance Images Using a Hybrid Deep Learning Approach - Özaltın, Öznur; Çobanbaş, Sezgi; Sırakaya, Yasemin; Güneş, Yuşa (Fırat University, 2025)
Alzheimer’s disease is one of the most serious diseases of our age. Early diagnosis is very important in this almost incurable disease. The progress of this disease will be slowed down by early diagnosis. This study goals to identify Alzheimer’s disease based on deep learning from Magnetic Resonance (MR) images. Convolutional Neural Networks (CNN), one of the deep learning algorithms, can automatically extract features from images. In this study, eight different CNN architectures were used to detect Alzheimer’s disease from MR images. NasNetMobile, the most successful of these architectures, was used as an automatic feature extractor, and 1056 features were extracted from its last layer. These features were classified through machine learning algorithms: Deep Neural Network (DNN), Support Vector Machine (SVM), Decision Tree, K-Nearest Neighbor, and Artificial Neural Network (ANN). Although high accuracy was achieved at this stage of the study, the minimum Redundancy Maximum Relevance (mRMR) approach was used for selecting features and robust results. Thus, 1056 features were reduced to 250. As a result, the classification performance of machine learning algorithms improved. The NasNetMobile-mRMR-DNN hybrid algorithm was the most successful in the detection of Alzheimer’s disease with an accuracy rate of 90.68%.

Alzheimer hastalığı, çağın en ciddi hastalıkları arasında yer almaktadır. Tedavisinin neredeyse bulunmadığı bu hastalıkta erken teşhis çok önemlidir. Erken teşhis edilmesi durumunda bu hastalığın ilerlemesi yavaşlayacaktır. Bu çalışmada, Alzheimer hastalığının derin öğrenme aracılığı ile Manyetik Rezonans (MR) görüntüler üzerinden tespit edilmesi amaçlanmıştır. Derin öğrenme algoritmalarından olan Evrişimli Sinir Ağları (ESA), görüntülerden otomatik özellik çıkarabilme yeteneğine sahiptir. Bu çalışmada, Alzheimer hastalığını MR görüntülerinden tespit etmede sekiz farklı ESA mimarisi kullanılmıştır. Bu mimarilerden en başarılı test sonucu veren NasNetMobile, otomatik özellik çıkarıcı olarak kullanılmış ve son katmanından 1056 özellik elde edilmiştir. Bu özellikler makine öğrenme algoritmalarından Derin Sinir Ağı (DSA), Destek Vektör Makinesi (DVM), Karar Ağacı, K-En Yakın Komşu, Yapay Sinir Ağı (YSA) ile sınıflandırılmıştır. Çalışmanın bu aşamasında yüksek doğruluk oranı elde edilse de sağlam sonuçlar için özellik seçim yöntemlerinden minimum Artıklık Maksimum İlişki (mRMR) yaklaşımından yararlanılmıştır. Böylece 1056 özellik 250’ye indirgenmiştir. Sonuç olarak, makine öğrenme algoritmalarının sınıflandırma performansı artmıştır. Alzheimer hastalığının tespitinde %90,68’lik doğruluk oranı ile en başarılı sonuç veren NasNetMobile-mRMR-DSA hibrit algoritması olmuştur.
Alzheimer Hastalığının Manyetik Rezonans Görüntülerden Hibrit Derin Öğrenme Yaklaşımı ile Otomatik Tespiti
Keywords: Deep Learning; Derin Öğrenme